Penguatan Literasi Hukum dalam Tata Kelola BUMDes Kalurahan Nglanggeran Menuju Desa Mandiri - Fakultas Hukum Universitas Negeri Surabaya; Intan Lovisonnya; Hananto Widodo; Sulaksono Sulaksono; Muh. Ali Masnun; Bachrul Amiq; Hikam Hulwanullah (Jurnal Darma Loka, 2025)
The legal literacy strengthening program for the governance of BUMDes Kalurahan Nglanggeran aims to enhance the legal capacity of BUMDes managers so they can perform institutional functions in an accountable, professional, and regulation-compliant manner. The methods employed include the Legal Literacy Approach and Participatory Action Research (PAR), involving active participation from BUMDes managers, village government, and local community through pre-test, post-test, focus group discussions, problem identification, and legal drafting sessions. The results indicate a significant improvement in legal understanding, demonstrated by a post-test score increase of more than 25% and active participation exceeding 80% of participants. These achievements affirm that legal literacy is not merely a transfer of knowledge but serves as a legal empowerment instrument that strengthens BUMDes governance as a legitimate and autonomous legal entity. Legal literacy thus becomes a fundamental pillar to prevent maladministration, enhance accountability, and ensure the sustainability of village enterprises based on the principles of good governance. The main recommendation of this program is the need for continuous legal assistance and collaborative efforts between village authorities, universities, and local stakeholders to establish an adaptive and progressive legal ecosystem toward an independent village.